p53 regulates the expression of histone modifiers to restrict stemness and maintain differentiated luminal identity in breast cancer - Yael Aylon; Noa Furth; Anna C. Pirona; Adi Lavie; Olga Fedorova; Ori Hassin; Nuno Padrão; Maxime Steinmetz; Avital Sarusi-Potuguez; Liat Fellus-Alyagor; Irit Shimoni; Bareket Dassa; et al. (Proceedings of the National Academy of Sciences, 2025)
Breast cancer is the leading cause of death in women under 50. The majority of breast cancers are estrogen receptor α-positive (ER+) and are commonly treated with hormonal therapies such as tamoxifen that inhibit ER activity. The TP53 tumor suppressor gene, encoding the p53 protein, is the most frequently mutated gene in breast cancer, and TP53 mutations are associated with diminished tamoxifen response and worse prognosis for breast cancer patients. Here, we report that in breast cancer cells p53 and ER cooperate to regulate the transcription of a set of genes encoding chromatin modifiers. The net result is a global increase in H3K4me3 and decrease in H3K9me3 chromatin marks. The resultant “open” chromatin is associated with increased transcription of luminal cell identity genes and enhanced tamoxifen sensitivity. Conversely, diminished p53 control of these chromatin modulators is associated with the evolution of tamoxifen resistance and cancer stem cell properties.